Quick as a cricket - Wood, Audrey; Wood, Don, 1945- ([New York] : Child's Play (International), 2007)
A young boy describes himself as "loud as a lion," "quiet as a clam," "tough as a rhino," and "gentle as a lamb.".
2.8
K-3
Keywords: Animals -- Juvenile fiction; Self-perception -- Juvenile fiction; Animals -- Fiction; Self-perception -- Fiction; Stories in rhyme; Animals -- Fiction; Self-perception -- Fiction; Stories in rhyme